THE SPECIFICS OF PARENT-TEACHER INTERACTION IN EARLY CHILDHOOD EDUCATION - N. L. Antonova (Russian State Vocational Pedagogical University, 2018)
Introduction. Early school education as a beginning stage of an individual's educational trajectory fosters an enabling environment for a child's personal, physical, intellectual and moral development. A productive interaction between pre-school educational organizations and parents is known to play the key role in the mentioned process.Aim. Based on the empirical-sociological materials of the research, this paper is aimed to identify specific features of interaction between parents and teachers as subjects of the system of early childhood education in large industrial cities.Methodology and research methods. The empirical basis of the research was a questionnaire survey conducted among parents (n=220), whose children attended pre-school institutions in Yekaterinburg, and semi-structured interviews with early school teachers (n=30). The teachers were interviewed using the method of systematic sampling. Results and scientific novelty. A serious divergence was identified with regard to how parents and teachers understand the goal of early school education. The social demand of parents consists in preservation and strengthening of physical health of the child, and teachers consider the development of pupils' abilities as their main task. The research revealed the main topic for discussion between parents and teachers to be organizational issues (due payments, leaving children in the morning, etc.). The conclusion is drawn that passive acceptance of the current situation prevails in teacher-parent interaction, rather than an active attitude to realization of the principles of partnership and cooperation. Parents' tight schedules become an impediment for building of partner relationship with their children's teachers and eventually prevent collaborative interaction between the two sides. Nevertheless, parents are shown to trust teachers and recognize the teachers' professionalism. This circumstance is seen as a founding principle for formation, reproduction and development of partner interaction of the subjects of preschool education.Practical significance. The obtained results can be applied when planning directions to advance the quality and performance of preschool education institutions. Thus, first to be considered is the organization of complex system work on acculturation of pedagogical culture of parents as well as development of special competences of the teachers, enabling them to successfully realize the principles of constructive cooperation with parental community for the purpose of full, prosperous and harmonious education of younger generation.